2006
DOI: 10.1039/b518269g
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced supramolecular chirality in side-chain liquid crystalline azopolymers

Abstract: A series of liquid crystalline homopolymers that have photoisomerizable cyanoazobenzene groups in the side chain has been synthesized and characterized. Thin films of these polymers have been processed in order to study the absorption spectra and circular dichroism responses after illumination with 488 nm circularly polarized light. The tendency of the azobenzene units to aggregate and the modification of the electronic spectra by illumination were studied by UV-vis spectroscopy. Illumination with circularly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 52 publications
(69 reference statements)
2
53
0
Order By: Relevance
“…[27] Moreover, the thermal stabilities of the photoinduced supramolecular chiral organizations were studied for glassy nematic and smectic polymers and it was concluded that the photoinduced structure is stable in the glassy state. [28] Chiral nematic liquid crystals that have periodic helical structures are able to selectively reflect CPL at a wavelength that depends on the helical pitch. CPL with the same handedness as the helix is Bragg reflected, whereas light with opposite handedness passes through.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Moreover, the thermal stabilities of the photoinduced supramolecular chiral organizations were studied for glassy nematic and smectic polymers and it was concluded that the photoinduced structure is stable in the glassy state. [28] Chiral nematic liquid crystals that have periodic helical structures are able to selectively reflect CPL at a wavelength that depends on the helical pitch. CPL with the same handedness as the helix is Bragg reflected, whereas light with opposite handedness passes through.…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] Recently, we detected a selective reflection in films of a nematic azopolymer by irradiation with CPL, but not in a homologous smectic one having the same chromophoric unit. [28] The work described here involved the characterization and properties of a glassy nematic azopolymer after irradiation with CPL by techniques used in the study of chiral liquid crystalline phases. A model of chirality transfer from chiral light to material is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Recently, a very large optical rotation has been reported for an amorphous azopolymer, [17] and the influence of liquid-crystalline structures has been discussed. [18] In this work, we have investigated the details of photoinduced supramolecular chirality in 'achiral' and 'amorphous' azobenzene polymer films as a function of the handedness and ellipticity of light. In addition, we demonstrate chiroptical switching mediated by the reversible conversion of the helical sense of the supramolecular structures upon changing the handedness of the incident light.…”
Section: Introductionmentioning
confidence: 99%
“…Their system consists of nonmesomeric V-shaped azobenzene arms and melamine derivative core. Oriol and coworkers investigated the photoinduced supramolecular order as a function of the chemical structure of the azobenzene polymer, and discussed it from the viewpoint of the glass transition temperature, the length of the spacer and the nature of the liquid crystalline phase [183]. They reported that a selective reflection was observed in the polymer having a nematic liquid crystalline phase but not in the polymer having a smectic phase.…”
Section: Chirality Switching and Amplificationmentioning
confidence: 99%
“…and circular dichroic plates [192]. Oriol and coworkers reported on the thermal stabilities of the photoinduced supramolecular chiral structures in nematic and smectic polymers, and concluded that the thermal stability above the glass transition temperature depends on the liquid crystalline nature of the polymer [183]. Sourisseau and coworkers used Jones' matrix formalism for detailed analysis of photoinduced chirality and concluded that the degree of photoinduced rotation angle can easily be controlled depending on the ellipticity of the excitation light [193].…”
Section: Supramolecular Chiralitymentioning
confidence: 99%